Metode Sorogan: Implementasi Dalam Pembelajaran Kitab Kuning di Pondok Pesantren Al-Mannan Bagik Nyaka - Muh. Ali Sadikin; Jamaludin; Muhsinin (Al-Riwayah : Jurnal Kependidikan, 2024)
Islamic boarding schools, as traditional educational institutions in Indonesia, play a significant role in preserving and developing the Islamic scholarly heritage. One commonly used teaching method in Islamic boarding schools is the sorogan method, particularly in studying the yellow book. This study aims to analyze the implementation of the sorogan method in teaching the yellow book at Al-Mannan Bagik Nyaka Islamic Boarding School, as well as to identify the supporting and inhibiting factors in this process. Using a qualitative descriptive-analytical approach, data were obtained through participatory observation, interviews, and documentation. The results show that, although the sorogan method is effective in accelerating students' progress in understanding the yellow book, there are several obstacles hindering the learning process, such as time and teacher constraints, teaching time indiscipline, and lack of confidence among students considered capable of guiding new students. Efforts have been made to overcome these obstacles, including regular evaluation meetings between the school leadership and teachers, coordination between capable students and teachers, formation of discussion groups among students, and inter-student group discussions. It is hoped that these findings will provide valuable contributions to enhancing the effectiveness of teaching the yellow book using the sorogan method in Islamic boarding schools, as well as offering a more comprehensive overview of the dynamics of learning in these traditional institutions.